Heterophase Interface Dominated Deformation and Mechanical Properties in Al‐Cu‐Li Alloys. Issue 6 (29th April 2021) - Wang, Shuo; Zhang, Chi; Li, Xin; Wang, Junsheng
Abstract: As a common phenomenon in multiphase systems, interfacial deformation has a significant impact on the mechanical properties of materials. By utilizing the brittle cleavage and plastic slip modes, the deformation mechanism is tracked and mechanical properties of precipitate/matrix and precipitate/precipitate heterophase interfaces are induced in third‐generation Al‐Li alloys, including δ'(Al3 Li)/α‐Al, θ'(Al2 Cu)/α‐Al, and δ'(Al3 Li)/θ'(Al2 Cu) (depending on the ultrafine δ'/θ'/δ' composite precipitate). Based on bond energy and ideal stress calculations under tensile and shear deformations, it is noted that the universal interface separating the two phases is not the weakest link in these systems. In δ'/θ'/δ', specifically, the defined coherent interface I closing to the δ' may become a weak cracking point under tensile loading. Whereas, the semi‐coherent interface II on the edge of the δ'/θ'/δ' tends to undergo interplanar slip along the [001] direction at relatively low shear stress. By releasing a partial dislocation under shear deformation, the local stable stacking fault can occur in this semi‐coherent interface. And the interface‐mediated plasticity within the ultrafine δ'/θ'/δ' composite precipitate could be expected to solve the origin of the strength‐ductility conflict in modern Al‐Li alloys. Besides, the electronic structures and atomic bonding are performed to reveal the mechanism behind the improved interface strength. Abstract : The semi‐coherent interface on the edge of the δ'/θ'/δ' composite precipitate tends to undergo interplanar slip along the [001] direction at relatively low shear stress. By releasing a partial dislocation under shear deformation, the interface‐mediated plasticity within the ultrafine δ'/θ'/δ' could be expected to solve the origin of the strength‐ductility conflict in modern Al‐Li alloys.